Quasiclassical Trajectory Study of Stereodynamics for Exchange Reactions $H'(D')+H(D)S$ (Journal of Atomic and Molecular Sciences, 2018)
Product Polarizations for the exchange reaction $H'+HS$ and its isotopic variantson an accurate $1A'$ potential energy surface have been studied at collision energiesof 10 kcal/mol by using the quasi-classical trajectory method (QCT). Product rotationalangular momentum distributions $P(θ_r)$ and $P(φ_r)$ are calculated in the center-of-mass (CM) frame. Moreover, three generalized polarization-dependent differentialcross sections (PDDCSs) are also computed. The results demonstrated that the isotopiceffect displays sensitive effect on the product vector correlations. The reactionmechanism was discussed based on the properties of stereodynamics and the reactivetrajectories.
Keywords: stereodynamics; Isotopic Effects; Quasiclassical Trajectory; Exchange Reaction.